INDONESIA ANALISIS ALOKASI DANA DESA (ADD) PADA PEMERINTAH DESA SUNGAI RANGIT JAYA KECAMATAN PANGKALAN LADA KABUPATEN KOTAWINGIN BARAT - -, Sareh; Rayhan, Ahmad (Yayasan Penelitian dan Pengabdian Masyarakat Sisi indonesia, 2024)
ABSTRACT Village is a small-scale government structure that exists in a community group. Sungai Rangit Jaya Village is located in the West Kotawaringin Regency, Central Kalimantan Province. This study aims to understand the procedures for using Village Fund Allocation (ADD) in the Sungai Rangit Jaya Village government, so the research data will be based on actual conditions and situations according to the reality in the field. The method used in the study in Sungai Rangit Jaya Village, Pangkalan Lada District, West Kotawaringin Regency is a qualitative approach with research subjects including the Village Head, Village Secretary, Head of Financial Affairs, Head of Planning Affairs, Head of Village Government Section, BPD, and the community living in the village. In implementing ADD management, Sungai Rangit Jaya Village has applied the following principles: accountability, transparency, aspiration, and participation. The results of the study indicate that the Village Fund Allocation has been carried out with the provisions in West Kotawaringin Regency. This is explained by the entire series of Village Fund Allocation management processes by the Sungai Rangit Jaya Village Government including the following stages: planning, budgeting, disbursement, distribution, utilization, supervision, and ADD accountability reports in accordance with the West Kotawaringin Regent Regulation Number 13 of 2024.